EMISSION INVENTORY OF CO, NOX, SO2, PM2,5 AND PM10 IN DEPOK CITY, WEST JAVA - Ardiandy Saputra, M.
Depok city is a city in West Java Province that has high economic activity. The physical development of the city and the establishment of industrial and educational centers are accompanied by the increasing use of motor vehicles that have the potential to produce pollutant emissions into the free air. This may happen if there is no unity of planning arrangements from the government in order to balance the development of the city with the maintenance of the environment. One method of preventing the decline in air quality levels in Depok City is to control air pollution based on emissions inventory. In this study, the emissions inventory was conducted for the Depok City area by focusing on calculating the emission load of carbon monoxide (CO), nitrogen oxide (NOx),sulfur dioxide (SO2)and Particulate Matter (PM2.5 and PM10). The sectors for scope of this study are the transportation, industrial, residential and agricultural sectors. The methods used in this emissions inventory is top-down using fuel consumption data in each sector between 2015 and 2020. The data was obtained from PT Pertamina, BPH Migas, PGN and the Central Statistics Agency. While the emission factors used refer to guidelines for developing emission inventory in East Asia 2011, EMEP / EEA Guidebook 2019 and GAINS. Inventory results from 2015 - 2020 show that the transportation sector is the main contributor to CO pollutants on average by 99,3% or 29522,6 tons / year, NOx averages 82,4% or 1490,18 tons / year, PM2.5 average of 96.2% or 92,69 tons / year and PM10 averages 96% or 97,1%. While the industrial sector became the main contributor of SO2 pollutants with an average of 45% or 2.6 tons / year. The 2017 emissions load will then be distributed spatially by applying geographic Information System (GIS) methods to the grid with a resolution of 2 km x 2 km using Arc GIS software. Spatial distribution results will show the areas with the highest emissions burden in Depok City are in Pancoran Mas, Beji, Cipayung and Cimanggis districts.